Probing the interaction of lysozyme with cardiac glycoside digitoxin: experimental and in silico analyses - Ali, Mohd Sajid; Al-Lohedan, Hamad A.; Bhati, Rittik; Muthukumaran, Jayaraman (Frontiers in Molecular Biosciences, 2023)
Digitoxin is a cardiac glycoside used to treat heart failure and heart arrhythmia. However, its therapeutic concentration range is very narrow. High doses of digitoxin are associated with severe side effects; therefore, it is necessary to develop the delivery system which can control the plasma levels of it. In this context, the binding of lysozyme, an important protein having many applications, with digitoxin has been studied to see the ability of the former as a carrier. The studies were carried out using both experimental and computational methods. The intrinsic fluorescence of lysozyme increased on the addition of digitoxin. Fluorescence results suggested that there was a strong interaction between lysozyme and digitoxin which was favored, mainly, by hydrophobic forces. Further, digitoxin affected the secondary structure of lysozyme slightly by causing the partial unfolding of lysozyme. The preferred binding site of digitoxin within lysozyme was the large cavity of the protein. Molecular docking studies also established the principal role of hydrophobic forces in the binding with a significant support of hydrogen bonding. Frontier molecular orbitals of free digitoxin and in complexation with lysozyme were also computed and discussed. The findings from molecular dynamics simulation studies elucidate that, when contrasted with the first and third conformations of the digitoxinbound lysozyme complex, the second conformation promotes structural stability, reduces flexibility, and enhances the compactness and folding properties of lysozyme. The overall study shows that lysozyme could act as a potential carrier for digitoxin in pharmaceutical formulations.